SEKOLAH ALAM BENGAWAN SOLO DENGAN PENDEKATAN EKOLOGI ARSITEKTUR DI KABUPATEN KLATEN - Hikmatyar Abdul Aziz; Bambang Triratma; Amin Sumadyo (Universitas Sebelas Maret Surakarta, 2016)
Design of the School of Natural Bengawan Solo in Klaten motivated by formal school education as children when space is in fact still can not be said to ideal for education and develop interest in the child's talents. Education became a fundamental necessity for everyone today. This then raises the idea to present alternative educational space able to accommodate the needs of children to learn, play, and explore. Empowering communities to be able to optimize the potential to become one of the important objects in presenting educational space. Bengawan Solo river and wood craft into the potential of rural communities Gondangsari, Juwiring, Klaten. Potentials possessed villagers Gondangsari not managed properly due to lack of containers in order to accommodate and develop this potential. Design issues are: how to design an alternative education space and bring the space community development based on the application of Ecological Architecture into the design of the School of Natural Solo. The method used is a method of architectural design that blends the essence of Ecological Architecture according to Heinz Frick and Kenneth Yeang in accordance with the design of the School of Natural Solo. Then blend the essence of Ecological Architecture into the design strategies in the design essence a result of interaction of school, nature, and potential kawaasan. The result is a draft design of an educational facility such as classrooms, laboratories of nature, community development space, exhibition space and its supporting buildings which also functions as a precedent alternative education for the visitors.